A comprehensive approach for skin recognition. (3rd April 2012) - Zhou, Zhi; Du, Eliza Y.; Lin, Yong; Delp, Edward J.
In this paper, we proposed a new skin recognition method for human identification. We designed an automatic segmentation method to extract region of interest from a face image, the 1-D Log-Gabor wavelet-based approach for skin feature extraction, and two fusion methods to improve the recognition accuracy. The experimental results show that the proposed method can achieve high recognition accuracy and has better performance than traditional face recognition methods.